THE INFLUENCE OF SERVICE QUALITY ON STUDENTS SATISFACTION AT PRIVATE UNIVERSITIES IN BANDAR LAMPUNG - Ratih Amelia; Vitratin - (Proceeding International Conference on Information Technology and Business, 2015)
The research is aimed at giving contribution to long-termresearches for private universities in Bandar Lampung indeveloping human resources to be empowered eithernationally or internationally by prioritizing the sustainableservice and academic system.It can be reached by using survey method throughquestionnaire to respondents, consisting of a list ofquestions on current problems faced by the researcher andasking respondents for responding the questions. Thismethod is used to know how far the service provided byuniversities in developing their students in BandarLampung.